2023
DOI: 10.1021/acsomega.2c08183
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Structural Modifications and Properties of Graphene Quantum Dots for Biomedical Applications

Abstract: Graphene quantum dots (GQDs) are carbon-based, zero-dimensional nanomaterials and unique due to their astonishing optical, electronic, chemical, and biological properties. Chemical, photochemical, and biochemical properties of GQDs are intensely being explored for bioimaging, biosensing, and drug delivery. The synthesis of GQDs by top-down and bottom-up approaches, their chemical functionalization, bandgap engineering, and biomedical applications are reviewed here. Current challenges and future perspectives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 136 publications
0
0
0
Order By: Relevance
“…For example, in the preparation of GQDs from carbon-containing wastes, Wang et al [62] used coffee grounds as raw material, Ding et al [63] used renewable lignin as raw material, and Tran et al [64] used gelatin as raw material, realizing the effective utilization of solid waste. A technique applicable to the preparation of large-scale nonfunctional GQDs has also been proposed, based on the principle that graphite suspensions are passed through micrometer-sized z-channels at high speeds and pressures to generate high shear rates, whereas millimetersized suspensions of graphite flakes are first exfoliated into micrometer-sized graphene, which is then further shrunken and fragmented into nanometer-sized GQDs [65]. Methods of preparing graphene quantum dots are still being researched, and we may see more efficient and environmentally friendly methods in the future.…”
Section: Chemical Vapor Deposition Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, in the preparation of GQDs from carbon-containing wastes, Wang et al [62] used coffee grounds as raw material, Ding et al [63] used renewable lignin as raw material, and Tran et al [64] used gelatin as raw material, realizing the effective utilization of solid waste. A technique applicable to the preparation of large-scale nonfunctional GQDs has also been proposed, based on the principle that graphite suspensions are passed through micrometer-sized z-channels at high speeds and pressures to generate high shear rates, whereas millimetersized suspensions of graphite flakes are first exfoliated into micrometer-sized graphene, which is then further shrunken and fragmented into nanometer-sized GQDs [65]. Methods of preparing graphene quantum dots are still being researched, and we may see more efficient and environmentally friendly methods in the future.…”
Section: Chemical Vapor Deposition Methodsmentioning
confidence: 99%
“…The doped nitrogen will resonate with the effective orbitals of GQDs and improve the electronic activity, which makes it easier to be doped into GQDs. It has been found that doping N atoms into the original nanomaterial enhances its PL behavior, leading to enhanced applications in biosensing, fluorescence imaging, and several other areas [65]. Common nitrogen sources generally include ammonia [74], dimethylformamide (DMF), nitric acid [74], melamine, and quadrol [75].…”
Section: Nitrogen Dopingmentioning
confidence: 99%
See 3 more Smart Citations